Australia's most imperilled vertebrates. (June 2022) - Garnett, Stephen T.; Hayward-Brown, Brittany K.; Kopf, R. Keller; Woinarski, John C.Z.; Cameron, Kerry A.; Chapple, David G.; Copley, Peter; Fisher, Alaric; Gillespie, Graeme; Latch, Peter; Legge, Sarah; Lintermans, Mark; et al.
Abstract: The likelihood of extinction within the next 20 years was determined for 47 Australian mammal, bird, reptile, frog and freshwater fish taxa previously identified as being highly imperilled. A 14-member expert elicitation panel, consisting of a mix of taxon experts and government managers of threatened species, estimated that there was a > 50% chance that nine taxa would be extinct by 2041. The panel estimated that there was a > 50% likelihood that a further 16 taxa (considered extant under Australian legislation), for which there are no recent independently verified records, are already extinct, with four almost certainly extinct. For five of these taxa, there was a > 50% chance that they would persist for 20 more years if they are currently extant, notwithstanding the lack of recent records. Most of the taxa considered occur within conservation areas and in south-eastern Australia, where human population density is highest. All the highly imperilled taxa occur wholly or partly in conservation reserves, within a total reserved area of 1994 km 2, 0.13% of the total area conserved in Australia. Highly imperilled taxa also occur on 313 km 2 of non-conservation government-owned land, and 242 km 2 of private land. The total area that needs management intervention to prevent extinction of Australia's most imperilled vertebrate taxa in the next 20 years represents 0.06% of the area of Australia's terrestrial and freshwater environments.